Setelah Guncangan Digital - Samiaji Bintang Nusantara; Ignatius Haryanto; Albertus Magnus Prestianta (Ultimacomm: Jurnal Ilmu Komunikasi, 2019)
Working as a journalist is still aspired by some of Indonesia’s young generation, called the millennials. However, the media industry landscape in Indonesia is rapidly changing in recent years due to digital disruption. Several printed media have to work hard to adopt digital tools as a publication platform to reach news consumer, while others have desperately managing to expand its audience applying convergence strategies. Meanwhile, some media industries which could not compete in the digital market have decided to stop their publication. Since 2014, there were several media stop operating their production. In many cases, the media closure is followed by termination of employment among journalists. This study finds that it has not only impacted the future of the former journalists but also has caused precariousness condition for a young journalist. These journalists were the young generation, or the millennials age 24-35 years. Some of the millennials had worked for more than a year and enjoyed the privilege as a journalist. But when digital disruption came and hit the media where they worked, most of these young age journalists had not registered nor joined in a labor union that could have helped advocate them when facing disagreement with the media company. Besides, from 2014 to 2017, it is a difficult time for the journalist to adapt in the midst of the transition from conventional media to digital media. Keyword: digital disruption, young journalist, media closure